Developing tools to measure community competence on IMCI program implementation in San Juan, Batangas. - Bibat, Paul Daniel; Barit, Jay-V James G.; Bugarin, Czariane F.; Eleazar, Vittorio V.; Glorioso, Justin Alvin S.; Jimenez, Aliana Christel A.; Lapides, Jomel G.; Medrano, Mark Virgil L.; Mendoza, Gerald Nelson P.; Rodrigo, Carlo Miguel M.; Santiago, Lariela Dianne S.
This research entitled “Developing Tools to Measure Community Competence on IMCI Program Implementation in San Juan, Batangas” aims to: (1) identify operationalized process indicators for the community competence of San Juan, Batangas on IMCI program implementation; (2) develop an evaluation tool based on the identified process indicators; (3) identify the process indicators for the involvement of the community partners and core group members in fulfilling their three major roles concerning the IMCI program; (4) develop evaluation tools that quantify and qualify the knowledge, skills, and attitudes of community partners and core group members in playing their roles; and (5) determine the validity and reliability of the developed evaluation tools.